Nuclear energy - Lusted, Marcia Amidon (Minneapolis, MN : ABDO Pub. Co., 2013)
As our worlds population grows, so to does our need for energy. Scientists seek the next breakthrough in new technology while constantly finding ways to make current solutions cheaper and more efficient. In this title, discover what nuclear energy is, its history, how we use it today, and how new technologies can contribute to our energy future. Learn how researchers are working to solve nuclear energys problems, including radiation dangers, handling nuclear waste, and making new plants more efficient, cheaper, smaller, and safer. Sidebars, full-color photos, full-spread diagrams, well-placed graphs, charts, and maps, stories highlighting innovations in action, and a glossary enhance this engaging title. Innovative Technologies is a series in Essential Library, an imprint of ABDO Publishing Company.
Nuclear energy at a glance -- The history of nuclear energy -- Radiation -- Creating nuclear energy -- Nuclear plants and reactors -- Nuclear waste -- The benefits of nuclear power -- A fresh look.
Keywords: Nuclear energy